Pengaruh Event Pariwisata, Digital Marketing, Harga , Dan Fasilitas Terhadap Keputusan Berkunjung Wisatawan Di Objek Wisata Pantai Watukarung Kabupaten Pacitan - Putri, Intan Sabrina Aziza; Arifin, Rois; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze and explain the Influence of Tourism Events, Digital Marketing, Prices, and Facilities on Tourist Decisions at Watukarung Beach Tourist Attraction, Pacitan Regency. The sample used in this study was 99 respondents obtained from the Slovin formula using the probablility sampling technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. The data testing used is simultaneous and partial hypothesis testing. The results of this study show that simultaneously the variables of Tourism Events, Digital Marketing, Prices, and Facilities have a positive and significant effect on the decision to visit. Partially, the variable of tourism events has a positive value and is not significant to the decision to visit partially, the variable of Digital Marketing has a positive and significant effect on the decision to visit partially, the price variable had a positive and significant effect on the decision to visit partially, the facility variable had a positive and significant effect on the decision to visit. Keywords: Tourism Events, Digital Marketing, Prices, Facilities, and Visiting Decisions.